Immune-related myocarditis characterized by malignant arrhythmia caused by conduction system involvement: case report and literature review - Zhan, Luying; Qin, Zhiquan; Yang, Liu; Chen, Yun (Frontiers in Oncology, 2025)
Immune checkpoint inhibitor (ICI)-related myocarditis has a low incidence but an extremely high mortality rate, and malignant arrhythmia caused by ICI therapy is even rarer. We report our experience of two patients with myocarditis with conduction system involvement after ICI therapy. Both patients developed myocarditis within a short period after the first ICI dose and they predominantly had conduction bundle involvement with minimal myocardial damage. One patient rapidly progressed from sinus rhythm to complete atrioventricular block, and the patient’s symptoms improved only after pacemaker implantation. The other patient experienced paroxysmal ventricular tachycardia, which was controlled by synchronous corticosteroid therapy. Despite the strong immune side effects caused by ICIs, both patients achieved good clinical outcomes. We also conducted a literature search to explore the pathological mechanisms underpining immune-related myocarditis, as well as discussing the treatment strategies for immune-related myocarditis with conduction system involvement.